Prevention of postpartum infectious and inflammatory complications in women with injuries of the lower parts of genital tract - Л. Б. Маркін; Г. Б. Семенина; К. Л. Шатилович; Г. Я. Кунинець; О. В. Шахова (Publishing House TRILIST, 2020)
Objective of the study: evaluation of the effectiveness of antimicrobial antiseptic drug Femiclean for prevention of wound infection in postpartum women with injuries of the lower parts of genital tract. Materials and methods. A clinical and laboratory examination of 65 postpartum women was carried out. I observation group consisted of 33 women who underwent surgical treatment for perineal rupture of the II degree or episiotomy. Processing of external genitalia with disinfectant solutions (potassium permanganate, chlorhexidine) three times a day for the first 2-3 days, dry treatment of the perineum sutures with iodine solution for 5 days was performed to these patients. II observation group consisted of 32 women with a perineal rupture of II degree or episiotomy, who in addition to the above-indicated preventive and therapeutic measures were prescribed vaginal Femiclean tablets for 5 days. Effectiveness of these measures was determined by presence of the postpartum complications (infiltration and suppuration in vaginal and perineum sutures), results of vaginal discharge microscopy (before and after treatment) and cytological smears from perineum sutures region (on the 5th day of the postpartum period). Results. A more significant improvement of the vaginal bacteriological status following the treatment with Femiclean was in II group patients as compared with women in group I. The favorable course of tissue regeneration in all patients of group II, which was clinically confirmed by the absence of suppuration and dehiscence of perineal wound edges, proves the effectiveness of the dequalinium chloride drug for prevention of wound infection. One of the advantages of local drug administration is the lack of significant adverse effects on the lactobacilli pool, that is important for restoration of vaginal normocenosis in the puerperal period. Conclusion. Topical application of the antiseptic drug Femiclean provides a 3-fold reduction in infectious and inflammatory complications incidence at trauma of the lower parts of genital tract.